Status of fast reactor research and technology development. - Stanculescu, A.; Monti, Stefano (International Atomic Energy Agency, 2012)
"Based on a recommendation from the Technical Working Group on Fast Reactors, this publication is a regular update of previous publications on fast reactor technology. The publication provides comprehensive and detailed information on the technology of fast neutron reactors. The focus is on practical issues that are useful to engineers, scientists, managers, university students and professors. The main issues of discussion are experience in design, construction, operation and decommissioning, various areas of research and development, engineering, safety and national strategies, and public acceptance of fast reactors. In the summary the reader will find national strategies, international initiatives on innovative (i.e. Generation IV) systems and an assessment of public acceptance as related to fast reactors."--Publisher's description.
"The IAEA officers responsible for this publication were A. Stanculescu and S. Monti of the Division of Nuclear Power"--Foreword.
Keywords: Fast reactors -- Technological innovations.; Fast reactors -- Cores.; Sodium cooled reactors.; Liquid metal cooled reactors.; Gas cooled reactors.; elektronické knihy; electronic books